Portuguese occupation of the coast of Morocco Far 818-996/1415-1587 (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study examines the Portuguese occupation of the coast of Morocco Al-Aqsa , which is governed by a set of data, which is near Portugal , and earlier emergence of the State of Portugal and the pursuit of big projects in Morocco for a variety of reasons, accompanied by many of the campaigns that covered in the study , was thus one of the first countries that sought on sites in the Maghreb where he occupied the city of Ceuta in Morocco in 1415 AD ,the great and the marina from Algeria ,but the defeat in the battle of Valley stores disappointed hopes and made them prey to the enemy was Spain , which is seeking to extend its influence over Morocco .